Crashing the party. Does STV help independents?. (July 2014) - Weeks, Liam
Parties tend to be wary of candidate-centred electoral systems, which is one factor why the use of the Single Transferable Vote (STV) is limited to a few cases. One source of this wariness is that STV is thought to favour non-party candidates, or independents, a claim based primarily on the experience of Ireland. The relative absence of independents in Australia and Malta, the other two countries using STV for national elections, challenges the merits of this reasoning. This study re-examines the nature of this causal link using constituency-level data from the Irish and Australian cases. The results indicate that there is not a great deal of evidence to support the hypothesis that STV favours independents, in particular because electoral system detail can affect a system's ability to realize expected consequences. While constituency size, ballot access and ballot design affect support for independents, it is not always in the expected manner. This suggests that the non-party phenomenon is more than just a by-product of electoral system effects.